Comparison of clast and matrix dispersal in till:: Charlo-Atholville area, north-central New Brunswick - Dickson, M.; Broster, B.; Parkhill, M. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2004)
ABSTRACT Striations and dispersal patterns for till clasts and matrix geochemistry are used to deﬁne ﬂow directions of glacial transport across an area of about 800km2 in the Charlo-Atholville area of north-central New Brunswick. A total of 170 clast samples and 328 till matrix samples collected for geochemical analysis across the region, were analyzed for a total of 39 elements. Major lithologic contacts used here to delineate till clast provenance were based on recent bedrock mapping. Eleven known mineral occurrences and a gossan are used to deﬁne point source targets for matrix geochemical dispersal trains and to estimate probable distance and direction of transport from unknown sources. Clast trains are traceable for distances of approximately 10 km, whereas till geochemical dispersal patterns are commonly lost within 5 km of transport. Most dispersal patterns reﬂect more than a single direction of glacial transport. These data indicate that a single till sheet, 1–4 m thick, was deposited as the dominant ice-ﬂow direction ﬂuctuated between southeastward, eastward, and northward over the study area. Directions of early ﬂow represent changes in ice sheet dominance, ﬁrst from the northwest and then from the west. Locally, eastward and northward ﬂow represent the maximum erosive phases. The last directions of ﬂow are likely due to late glacial ice sheet drawdown towards the valley outlet at Baie des Chaleurs.